Foul play own goal - Palmer, Tom (Puffin London, 2011)
Meet Danny Harte. Football fan and crime detective. Danny loves his local team, City FC. So when everyone starts following the Italian team Forza FC, Danny is angry. His club is in jeopardy and needs their support. Danny decides to investigate the sudden popularity of the new team - starting with Forza's billionaire owner - that's when the danger really kicks off ... Can Danny uncover the sinister reasons behind Forza's success - and save City at the same time?